Overtreatment in treatment of cervical intraepithelial lesions - N. Kashtalian; I. Gladchuk; N. Rozhkovska; A. Volyanska (Kazimierz Wielki University, 2018)
Due to the long precancerous phase cervical cancer can be prevented by screening and early detection using various procedures, mainly Pap smear. Updated screening and management guidelines emphasize the precision of diagnosis and use estimates of risk to avoid overtreatment or undertreatment. The aim of the study was to analyze overtreatment in the current approach to cervical precancer treatment in Ukraine. Materials and Methods. We performed retrospective analysis of 80 case histories of patients who underwent excisional treatment of cervix and had pathological cytological smears. Results. In our study overtreatment rate of high‐grade cervical smear and high‐grade colposcopic impression was 41.18%, of low‐grade cervical smear and high‐grade colposcopic impression was 81.82%, of high‐grade cervical smear and low‐grade colposcopic impression was 67.86%, of low‐grade cervical smear and low‐grade colposcopic impression was 87.50%. Conclusions. Overtreatment rate of cervical intraepithelial lesions is currently very high and calls for further diagnostic methods. The use of HPV testing and targeted biopsy could improve diagnostic efficacy and allow to avoid unnecessary excisional treatment.